LPSK-Establishing State Presence in Protection of Witnesses and Victims, inclusive of Sexual Violence Crimes - Iskandar, Livia Istania (Jurnal Perempuan, 2021)
The Indonesian Witness and Victim Protection Agency (LPSK in Indonesian) was established based on Law No.13/2006 Protection of Witness and Victims, which was later amended by Law No 31/2014. It is an independent non-structural agency headed by seven commissioners for 5-year terms. One of the Agency’s priority crimes is sexual violence. The Agency protects witnesses, victims, whistleblowers, justice collaborators, and experts. For the years 2019-May 2021, the Agency has given protection to a total of 984 victims of sexual crimes, consisting of 67 percent children and 33 percent adults. Out of that, 78 percent are female victims compared to 22 percent male victims. Based on Law No. 31/2014, there are 16 types of witness and victims’ rights. The three most sought-after protection programs for victims of sexual violence are Procedural Rights, Psychological Rehabilitation, and Restitution Facilitation. For prevention programs, we need to learn who are sexual violence perpetrators.